2019
DOI: 10.1121/1.5101676
|View full text |Cite
|
Sign up to set email alerts
|

Task-evoked pupillary response to completely intelligible accented speech

Abstract: Listening to second language- (L2-) accented speech is often described as an effortful process, even when L2 speakers are highly proficient. This increase in listening effort is likely caused by systematic segmental and suprasegmental deviations from native-speaker norms, which require additional cognitive resources to process (Van Engen and Peelle, 2014). In this view of speech perception, even when an L2 speaker is completely intelligible (i.e., their words can all be correctly identified), perception noneth… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
4
0

Year Published

2020
2020
2020
2020

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(5 citation statements)
references
References 23 publications
(32 reference statements)
1
4
0
Order By: Relevance
“…Consistent with our hypothesis, the significant main effect of accent indicated that on average, pupil dilation was greater for nonnative- relative to native-accented speech within the time window of interest (β = 115.50, SE = 34.43, t = 3.36, p = .001; Figure 3). Further, the significant interaction between accent and the linear polynomial time term indicated that pupil dilation increased more rapidly after sentence onset for nonnative- relative to native-accented speech (β = 566.92, SE = 88.33, t = 6.42, p < .001), consistent with previous research (McLaughlin & Van Engen, 2020).…”
Section: Resultssupporting
confidence: 90%
See 4 more Smart Citations
“…Consistent with our hypothesis, the significant main effect of accent indicated that on average, pupil dilation was greater for nonnative- relative to native-accented speech within the time window of interest (β = 115.50, SE = 34.43, t = 3.36, p = .001; Figure 3). Further, the significant interaction between accent and the linear polynomial time term indicated that pupil dilation increased more rapidly after sentence onset for nonnative- relative to native-accented speech (β = 566.92, SE = 88.33, t = 6.42, p < .001), consistent with previous research (McLaughlin & Van Engen, 2020).…”
Section: Resultssupporting
confidence: 90%
“…The results from the two tasks were largely consistent with one another, providing converging evidence that (1) processing nonnative-accented speech requires greater listening effort than processing native-accented speech, as indicated by a main effect of accent, (2) the amount of listening effort required to process speech decreases rapidly with exposure, as indicated by a main effect of trial number, and (3) the reduction in listening effort over time may occur more rapidly for nonnative relative to native speech, as indicated by an interaction between accent and trial number in Experiment 2. Thus, it appears that although processing nonnative-accented speech requires greater listening effort than processing native-accented speech—even when intelligibility is equated across these conditions—these differences become less pronounced with exposure (replicating and extending the findings of McLaughlin & Van Engen, 2020). We did not explicitly test whether differences in effort between the native and nonnative conditions persisted following adaptation, but visual inspection of Figures 1 and 4 suggest that listeners still expended greater effort in the nonnative condition following adaptation.…”
Section: Discussionmentioning
confidence: 55%
See 3 more Smart Citations